ANALISIS STRATEGI PRODUK, HARGA, PROMOSI DAN TEMPAT TERHADAP KEPUASAN PELANGGAN WARUNG KOPI DI RANTAUPRAPAT - Suarni, Eka; Hasibuan, Desmawaty; Marto Hendry, Raja Saul (JURNAL MANAJEMEN AKUNTANSI (JUMSI), 2021)
This study aims to determine the Product Strategy Analysis, Price, Promotion and Place on Customer Satisfaction at Millennial Coffee Shop Rantauprapat. Data collection in this study was carried out through survey approaches, interviews and documentation. This study had a sample of 50 respondents using the Slovin method. The data analysis tool used in this study used SPSS (Statistical Product Software Solution). Data analysis techniques in this study are descriptive analysis, multiple linear regression analysis, hypothesis testing using partial significance test (test), simultaneous significant testing (F test), and testing the coefficient of determination (R2). Whereas the F test result is 5,944 with a significant level of 0,000 while the F table value is 2.58. If compared to the f count 5,944> f table 2.58 at Î±5%, the conclusion is that simultaneously the Product, Price, Promotion, and Place variables have a positive and significant effect on Customer Satisfaction, that the t value for the product variable is -2.693, the price is 4.020, the promotion is -1.518, and the place is 1.217 with a significant value for each independent variable (3.587), (0.001). As for the t table value in the table statistical distribution t with the level oftestÎ± = 5% 2-party test and dk = nk, 50-5 = 45, it is obtained t table of 1679.